The Effect of Group Guidance Services with the Premack Principal Technique to Reduce Verbal Abuse of Mobile Legends Players - Dhea Aulia Putri; Abdul Aziz Rusman (SCHOULID: Indonesian Journal of School Counseling, 2025)
Verbal abuse behavior in the Mobile Legends game significantly impacts students' mental health, leading to decreased self-esteem, increased stress, anxiety, and a higher risk of depression. This study analyzes the effectiveness of group guidance services using the Premack Principle technique to reduce verbal abuse among Mobile Legends players at SMP Negeri 1 Natal. Employing a quantitative approach with a Nonequivalent Control Group design, the study involved 20 students with high verbal abuse levels, selected through purposive sampling. Data were collected using a 16-item Likert-based scale and analyzed with the Shapiro-Wilk normality test and independent sample t-test via SPSS 25.0. Results indicated a significant decrease in the experimental group's average verbal abuse score from 68.90 (pretest) to 33.10 (posttest), while the control group showed minimal change. The findings confirm the effectiveness of the intervention, highlighting the need for similar programs in schools to foster healthier interactions among students.